SCIENTIFIC-PRACTICAL AND STRATEGIC BASES OF IMPROVING PEDAGOGICAL-PSYCHOLOGICAL COOPERATION IN THE INTEGRATION OF SCHOOL AND PRE-SCHOOL EDUCATIONAL ORGANIZATIONS IN THE CONTEXT OF CONTINUOUS EDUCATION ON THE BASIS OF INNOVATIVE LOGISTICS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, innovations in the field of education, educational technologies that develop in education, innovations in the field of education, educational conditions, the requirements of society and the state, traditional pedagogical technologies that implement the ideology of reproductive education, and innovative factors issues of coordination, coordination and development of school and MTT activities are analyzed scientifically and pedagogically